X chromosome heterochromatic pattern and nucleolar synthesis in pupal ovaries of Aedes aegypti - De Cássia De Sousa, Rita [UNESP]; De Campos Bicudo, Hermione Elly Melara [UNESP] (My University, 1998)
C-banding and silver-staining techniques were used to examine pupal ovaries of Aedes aegypti from São José do Rio Preto (Brazil). Silver staining in ovary cystocytes showed two basic patterns relative to the nucleolar morphology: viz (1) a single, compact small body; and (2) multiple bodies encompassing large nuclear areas. These two types of cystocytes were present in the ratio of 7:1, which is the same as the number of nurse cells and oocytes, respectively, in each follicle. This suggests the possibility of eventually using such a nucleolar morphological difference to recognize both cell types in developmental stages before emergence. Silver nitrate staining in metaphase chromosomes revealed centromeric bands on all six chromosomes. The C-banding pattern in metaphase chromosomes showed an intercalary band in one of the X arms, as described previously in other populations. In ovary cystocytes (pachytene stage) this C-positive band seemed to consist of two chromomeres. Phase contrast microscopy showed that the nucleolus was associated with the distal chromomere of this intercalary C-band, indicating that the nucleolus organizer region was located in that part of the heterochromatic band.
Keywords: Aedes aegypti; Heterochromatic pattern; Nucleolar organizer regions; Nucleolus